To senmiddelalderlige relieffer og deres grafiske forelegg: Stilkritiske refleksjoner omkring Mariafremstillingene i Eksingedalskapet og Rollagtavlen – eller: En mulig virus i operativsystemet - Achen, Henrik v. (Hikuin, 1999)
Two Late Medieval Enthroned Madonnas and Their Engraved Model. Methodological Reflections on Dating and Attribution Based on Analysis of Style – or: a Possible Virus in the Operative System By Henrik von Achen Since the dawn of art history as a discipline, the method of analysing stylistic features of a work of art in order to discern when it was made, where and if possible by whom, has been fundamental in the work of arthistorians. In its essence the method is comparative, basing its analysis on the phenomenon of «visual likeness» between works of art. While one may object to such a method that its too subjective, too easily the victim of the art historian’s need to discover, attribute or date, it cannot be denied that the method is still fundamentally necessary in view of the vast amount of anonymous medieval works of art. The ‘modus operandi’ of this comparative method is based on the assumption that if works of art look alike, this indicates that they are somehow genetically linked. Discussing a late medieval enthroned Virgin and Child appearing in two different variations in southern Norway, Eksingedalen and Rollag, this paper points to a problem caused by the workshops’ use of mechanically reproduced models, engravings or woodcuts, since the beginning of the 15th century. These two sculptures, probably produced in northern Germany in the decades around 1500, are based on an engraving from c. 1465 by the «Master ES». This use of an older model made in quite a different area, will necessarily cause a sort of «genetic leap», where stylistic features appear with no logic connection to the workshop. If one bases an attribution solely on visual similarity, the fact that such models where often used constitutes a pitfall, where the «genetic leap» connects age, master and area in an arbitrary way, appearing to belong to the characteristics of a workshop or a woodcarver, but actually destroying any connection between visual similarity and genetics. However, as the method of style analysis is still a necessary tool, art historians should not dismiss its legitimate role in contemporary scholarship, but try to refine it to make it more aware of the historical facts of medieval art production, as well as of the visual conventions of an age. The method may be refined simply by gaining more knowledge of the many various reasons why two works of art to some extent came to look like each other. The competence to analyse style and form, the knowledge of the field in question, the shear ‘connaisseurship’, is thus not to bedismissed as outdated, but to be developed and refined, not least concerning its socio- economic aspects.